PENGEMBANGAN MEDIA FUN THINKERS BUSY BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 SEKOLAH DASAR - Suryaman; Ni’mah, Lailun (Jurnal PGSD, 2022)
This study aims to develop a valid Fun Thinkers Busy Book learning media product that can improve student learning outcomes on the subject of the beauty of the unity and integrity of my country. This study uses the Research and Development (R&D) method. Data collection techniques used are written tests, interviews. questionnaire and documentation. The results of the study show that the Fun Thinkers Busy Book media is suitable for use as a learning medium with several revisions based on corrections by media experts and material experts. The percentage of eligibility from media experts is 100% with very appropriate information and 100% from material experts. The results of the small group trials showed an increase in learning outcomes by 75%. Meanwhile, in the large group trial, there was an increase of 73.33%. The results of the student response questionnaire show a percentage of 100% with a very decent description. So it can be concluded that the Fun Thinkers Busy Book media is suitable for use as a learning medium on the beauty of the unity and unity of the Republic of Indonesia to improve learning outcomes for 4th grade elementary school students.